1976
DOI: 10.1177/036354657600400602
|View full text |Cite
|
Sign up to set email alerts
|

A study of thigh muscle weakness in different pathological states of the lower extremity

Abstract: It has long been recognized that limb injury produces relative atrophy and weakness, which can cause an increased susceptibility to reinjury. In 1964, Bender et all concluded from a study of the lower body strength of 806 West Point Cadets that &dquo; ... individuals who have strength differences greater than 10% between the limbs, and also those in the lower quartile strengthwise, are more likely to be injured than are those who possess normal strength levels.&dquo; These studies were limited to isometrics, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
0
9

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(68 citation statements)
references
References 2 publications
3
56
0
9
Order By: Relevance
“…This meta-analysis provides evidence that bilateral postural control impairments are present following an acute lateral ankle sprain and support the findings of Evans et al [15] in a true prospective study indicated that following an acute lateral ankle sprain postural control deficits in the uninvolved limb take approximately seven days to be resolved whereas deficits in the involved limb typically take at least four weeks [15]. Further, our findings support the growing breadth and depth of the literature that indicates centrally mediated changes occur after lateral ankle trauma and suggest that these changes may be the underlying cause of CAI [11,15,23,25,42,[51][52][53][54][55][56][57][58][59][60].…”
Section: Postural Deficits Meta-analysis Ii: Uninvolved Limb Versus Csupporting
confidence: 72%
See 1 more Smart Citation
“…This meta-analysis provides evidence that bilateral postural control impairments are present following an acute lateral ankle sprain and support the findings of Evans et al [15] in a true prospective study indicated that following an acute lateral ankle sprain postural control deficits in the uninvolved limb take approximately seven days to be resolved whereas deficits in the involved limb typically take at least four weeks [15]. Further, our findings support the growing breadth and depth of the literature that indicates centrally mediated changes occur after lateral ankle trauma and suggest that these changes may be the underlying cause of CAI [11,15,23,25,42,[51][52][53][54][55][56][57][58][59][60].…”
Section: Postural Deficits Meta-analysis Ii: Uninvolved Limb Versus Csupporting
confidence: 72%
“…For example, BullockSaxton et al [51] and Bullock-Saxon [11] reported altered proximal muscle activation patterns following acute lateral ankle sprains. Additionally, Hubbard et al [25], Nicholas et al [59], and Friel et al [56] all reported hip musculature strength deficits in CAI patients while Sedory et al [60] revealed bilateral hamstring inhibition in CAI patients. Even though the exact mechanisms of these alterations remain unknown, a plausible explanation focuses on altered motor control programs [3].…”
Section: Postural Deficits Meta-analysis Ii: Uninvolved Limb Versus Cmentioning
confidence: 99%
“…[22][23][24] Furthermore, weakness and alteration of neuromuscular activation patterns in the lumbopelvic-hip complex and the lower extremity have been documented in patients with joint injuries that are distant from the affected musculature. [25][26][27][28][29][30] The injury-related neural effect on muscle activation can apparently occur in either a distal-to-proximal or proximal-to-distal direction. Lower extremity dysfunction increases susceptibility to low back injury, 31 and susceptibility to lower extremity injury appears to be increased by low back dysfunction.…”
mentioning
confidence: 99%
“…These investigations, producing consistent results, have proposed a possible implication of hip joint muscle activation response to gluteus maximus (BullockSaxton, 1994;Bullock-Saxton et al, 1994;Nicholas et al, 1976) medius (Beckman and Buchanan, 1995) and hip weakness in abduction and adduction position (Nicholas et al, 1976) during isokinetic tests. Recently, Van Deun et al (2007) found a significantly later onset for ankle, hip and hamstring muscles in subjects with chronic ankle instability compared with controls passing from doubleleg to single-leg stance.…”
Section: Introductionmentioning
confidence: 63%